Chinese school teachers' perceptions of continuous professional development training in Melaka Teacher Training Institute. A narrative design - Cheok, Mei Lick (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
This paper looked at the effectiveness of Continuous Professional Development (CPD) training in a blended learning environment. The study was carried out as the researcher would like to obtain feedback regarding their training sessions. As teacher educators, it is important for us to know what worked and what not during our training. Participants were teachers from four Chinese vernacular schools whom were asked to attend the course as part of the government’s initiatives to increase the number of trained English teachers in the vernacular schools. Data were gathered from participants’ reflections, questionnaires and interviews. They were analysed using Burnard’s (1991) thematic content analysis. Findings reflected Robert’s (1998) types of learning experience that was essential in CPD training. Direct experience, second-hand experience, input of new information, self-awareness and processing of experience and input are all part of important ingredients in ensuring effective CPD training.